2019
DOI: 10.1002/1873-3468.13319
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+‐free ATP regulates the processivity of native cytoplasmic dynein

Abstract: Cytoplasmic dynein, a microtubule‐based motor protein, is responsible for many cellular functions ranging from cargo transport to cell division. The various functions are carried out by a single isoform of cytoplasmic dynein, thus requiring different forms of motor regulation. A possible pathway to regulate motor function was revealed in optical trap experiments. Switching motor function from single steps to processive runs could be achieved by changing Mg2+ and ATP concentrations. Here, we confirm by single m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…The Mg 2+ concentration, remarkably constant and low in cytoplasm but tenfold higher in mitochondria, mediates ADP/ATP exchange between the cytosol and the matrix [ 135 ]. Mg 2+ and ATP form a stable Mg–ATP complex, and the degree of complex formation depends on the ratio of Mg 2+ to ATP [ 136 ]. Since Mg–ATP is in a balanced state with free Mg 2+ in cells, it has been suggested that a decrease in free Mg 2+ may be a primary cause of low intracellular ATP [ 137 ].…”
Section: Mitochondrial Mg 2+mentioning
confidence: 99%
“…The Mg 2+ concentration, remarkably constant and low in cytoplasm but tenfold higher in mitochondria, mediates ADP/ATP exchange between the cytosol and the matrix [ 135 ]. Mg 2+ and ATP form a stable Mg–ATP complex, and the degree of complex formation depends on the ratio of Mg 2+ to ATP [ 136 ]. Since Mg–ATP is in a balanced state with free Mg 2+ in cells, it has been suggested that a decrease in free Mg 2+ may be a primary cause of low intracellular ATP [ 137 ].…”
Section: Mitochondrial Mg 2+mentioning
confidence: 99%